A mold for testing the adhesion of aluminum plate to composite material and a testing method thereof

CN123008431APending Publication Date: 2026-10-30CHINA MASCH PRECISION FORMING IND TECH RES INST (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611028064.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种用于铝板与复合材料粘合力测试的模具及其测试方法,以解决现有技术中滚筒剥离检测样板的成型模具与样板匹配度不高、铝板与复合材料的粘合力检测难以快速进行的技术问题

Benefits of technology

本发明提供了对预浸料片和铝板进行限位的双层限位结构模具,此成型模具将实现样本“定位”与“定厚”功能的协同,不仅解决了制样困难、样品一致性差的问题,同时能够确保样品制备质量,保障了后续粘合力测试结果的准确性,为快速判定和优化铝板表面处理工艺提供了可靠的硬件基础;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123008431A_ABST
    Figure CN123008431A_ABST
Patent Text Reader

Abstract

The present application relates to the field of material testing and characterization, and discloses a mold for testing the adhesion between an aluminum plate and a composite material, characterized in that it comprises an upper mold plate, a lower mold plate and an intermediate mold plate; the upper mold plate and the lower mold plate are face-symmetrical structures; the intermediate mold plate is a flat plate with a hole design, and at least one hole for accommodating a prepreg sheet and an aluminum plate is arranged inside; two end plates are arranged in the hole, and each end plate extends upward from the bottom surface of the hole; a column protruding upward is arranged on the top surface of each end plate, and the column and the end plate form a double-layer limiting structure; and a method for testing the adhesion between an aluminum plate and a composite material, which is performed on a test sample prepared by the mold. The present application not only solves the problems of sample preparation difficulty and poor sample consistency, but also ensures the sample preparation quality and the accuracy of the adhesion test results in the adhesion test between the aluminum plate and the composite material, thereby providing a reliable hardware basis for quickly determining and optimizing the surface treatment process of the aluminum plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials testing and characterization technology, specifically to a mold and testing method for testing the adhesion force between aluminum plates and composite materials. Background Technology

[0002] Existing aluminum plate surface treatment processes and epoxy resin-based composite materials have difficulty achieving a peel strength of 250 (N*mm) / mm on the lower pallet roller. The adhesion is weaker than that of electrophoretic steel plates and epoxy resin-based composite materials. This is because aluminum plate surface treatment processes are complex and diverse. Therefore, when determining the adhesion between aluminum plates and composite materials, it is necessary to continuously conduct sandwich structure roller peel strength tests until the optimal aluminum plate surface treatment process can be detected.

[0003] In existing technologies, the roller peel strength test of sandwich structures requires the preparation of a roller peel template of the sandwich structure. Since the roller peel template consists of two layers of different materials, structures and lengths, it is difficult to use simple heating and pressurizing devices and simple U-shaped molds to press out qualified and aesthetically pleasing templates during the template preparation process. Manual bonding is usually used, but if the bonding and layout are not handled carefully, the finished template will be damaged, which will greatly affect the efficiency of the test.

[0004] Furthermore, unprofessional molds not only affect the adhesion between the aluminum plate and the composite material, causing a decrease in the mechanical properties of the sandwich structure sample, but also affect the uniformity of the samples, thus further reducing the mechanical properties of the sandwich structure sample. Multiple parallel tests are required when conducting adhesion force testing to eliminate the influence of sample differences, which in turn leads to a decrease in the efficiency of adhesion force testing between the aluminum plate and the composite material.

[0005] Therefore, there is a need for a test method that can quickly determine the adhesion between aluminum plates and composite materials, so as to quickly and effectively determine the optimal surface treatment process for aluminum plates, and to provide a molding die that can quickly and effectively prepare qualified roller peel test samples. Summary of the Invention

[0006] The purpose of this invention is to provide a mold and a testing method for testing the adhesion force between aluminum plates and composite materials, so as to solve the technical problems in the prior art where the matching degree between the forming mold and the sample of the roller peel test sample is not high and the adhesion force test between aluminum plates and composite materials is difficult to be carried out quickly.

[0007] To solve the above-mentioned technical problems, the present invention specifically provides the following technical solution: A mold for testing the adhesion force between aluminum plates and composite materials includes an upper template, a lower template, and an intermediate template; The upper template and the lower template are surface-symmetrical structures; The intermediate template is a flat, hollowed-out design, with at least one hole inside for accommodating the prepreg sheet and aluminum plate; The end plate protrudes from the bottom surface of the hole, and the height of the end plate is less than the thickness of the hole, so that the top surface of the end plate is lower than the top surface of the hole; a column protrudes vertically upward from the top surface of each end plate, and the top surface of the column is flush with the top surface of the hole. The end plate and the column are stacked sequentially along the thickness direction of the hole, so that the top surface of the end plate forms a first limiting step surface that is lower than the top surface of the hole, and the top surface of the column forms a second limiting step surface that is flush with the top surface of the hole. The first limiting step surface and the second limiting step surface are staggered in the thickness direction to form the double-layer limiting structure. The first limiting step surface is used to limit the position of the aluminum plate in the thickness direction, and the second limiting step surface is used to limit the position of the prepreg sheet in the thickness direction, so that the aluminum plate and the prepreg sheet are respectively limited to different thickness layers in the mold closing state, so as to achieve layered limiting and gapless bonding of the aluminum plate and the prepreg sheet in the thickness direction.

[0008] Furthermore, the prepreg sheet is provided with positioning holes that are adapted to the column body. The prepreg sheet is fitted onto the column body through the positioning holes in a snap-fit ​​manner, thereby achieving precise positioning of the prepreg sheet in the horizontal direction. The aluminum plate is placed in the groove area between two opposing end plates. The inner sidewall of the end plate forms a horizontal limit on the aluminum plate. The bottom surface of the aluminum plate is in contact with the top surface of the end plate to achieve the positioning of the aluminum plate in the thickness direction. The double-layer limiting structure simultaneously constrains the prepreg sheet and the aluminum plate in both the horizontal and thickness directions, ensuring that the sample obtained after molding and curing has neat edges and accurate dimensions, eliminating the need for trimming or grinding.

[0009] Furthermore, the height of the end plate is equal to the thickness of the aluminum plate, and the height of the column is equal to the thickness of the prepreg sheet. After the mold is closed, the distance between the inner surface of the upper mold plate and the inner surface of the lower mold plate is forcibly locked to the standard total thickness of the sum of the aluminum plate thickness and the prepreg sheet thickness.

[0010] Furthermore, the intermediate template has a number of holes inside, which are evenly spaced along the length of the intermediate template. Each hole is provided with an end plate and a column, so that several samples can be prepared simultaneously in one molding cycle, and the curing temperature history, pressure distribution and resin flow behavior of several samples are consistent in the same molding cycle.

[0011] Furthermore, the intermediate template is provided with a polytetrafluoroethylene coating.

[0012] Furthermore, the inner surfaces of both the upper and lower templates are mirror-polished.

[0013] Furthermore, both the upper and lower templates have irregular protrusions extending outwards along their edges, which facilitate mold opening and sampling.

[0014] A method for testing the adhesion force between an aluminum plate and a composite material, the method being performed based on a test sample prepared using the aforementioned molding die, comprising the following steps: S100. Provide an aluminum plate and a prepreg sheet, and cut and perforate the prepreg sheet to form positioning holes that can precisely fit with the subsequent mold. S200. The prepreg sheet is fastened onto the column of the mold through the positioning hole, and the aluminum plate is placed between the end plates of the mold. The double-layer limiting structure on the mold is used to simultaneously achieve precise positioning of the prepreg sheet and the aluminum plate and gapless limiting in the thickness direction. S300. The upper, middle and lower three-layer templates of the mold are combined to form a three-piece sandwich structure to forcibly lock the prepreg sheet. S400. The three-piece sandwich structure is placed in a molding equipment for molding, so that the prepreg sheet is cured and bonded to the aluminum plate to obtain a sample. The sample is taken out and clamped onto the corresponding matching fixture for a peel test.

[0015] Furthermore, in step S200, the lower surface of the prepreg sheet is attached to the top surface of the column, the bottom surface of the aluminum plate is attached to the top surface of the end plate, and the upper surface of the aluminum plate is attached to the inner surface of the upper template, so that the prepreg sheet and the aluminum plate are positioned without gaps in the thickness direction, and the total thickness of each sample is forcibly locked to a standard thickness value, ensuring that the thickness of multiple samples prepared in the same batch is consistent.

[0016] Furthermore, the prepreg sheet is an epoxy resin-based glass fiber prepreg sheet; The peeling experiment is a roller peeling experiment, and the fixture is a roller peeling experiment fixture.

[0017] Compared with the prior art, the present invention has the following advantages: This invention provides a double-layer limiting structure mold for limiting prepreg sheets and aluminum plates. This forming mold will realize the synergistic function of sample "positioning" and "thickness determination", which not only solves the problems of difficult sample preparation and poor sample consistency, but also ensures the quality of sample preparation and guarantees the accuracy of subsequent adhesion test results, providing a reliable hardware foundation for rapid determination and optimization of aluminum plate surface treatment process. The testing method disclosed in this invention can further eliminate the interference of variables in the sample preparation process, so that the fluctuation of the measured data mainly comes from the difference in the surface treatment process of the aluminum plate itself, rather than the sample preparation error, thereby accelerating the efficiency of screening the best aluminum plate surface treatment process. Attached Figure Description

[0018] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.

[0019] Figure 1 A schematic diagram of the overall structure of the mold is provided for the embodiments of this application; Figure 2 A schematic diagram of the structure of the intermediate template in the mold is provided for the embodiments of this application; Figure 3 A schematic diagram of the structure of the holes in the mold is provided for the embodiments of this application; Figure 4 A schematic diagram of the side structure of the end plate of the mold is provided for the embodiments of this application; Figure 5 A schematic diagram of the structure of the prepreg sheet is provided for the embodiments of this application; Figure 6 A schematic diagram of the side structure of the prepreg sheet bonded to the aluminum plate is provided for an embodiment of this application; Figure 7 A schematic diagram of the upper template in the mold is provided for the embodiments of this application; Figure 8 This is a flowchart illustrating the method for testing the adhesion between an aluminum plate and a composite material, as provided in an embodiment of this application.

[0020] The reference numerals in the figure are as follows: 1-Upper template; 11-Irregular protrusions; 2-Intermediate template; 21-Hole; 22-End plate; 23-Column; 3-Below template; 4-Prepreg sheets; 5-Aluminum sheet. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0022] like Figures 1-7 As shown, this mold includes: an upper template 1, a lower template 3, and a middle template 2; The upper template 1 and the lower template 3 are surface-symmetrical structures; The intermediate template 2 is a flat, hollowed-out design, with at least one hole 21 inside for accommodating the prepreg sheet and aluminum plate; The end plate 22 protrudes from the bottom surface of the hole 21, and the height of the end plate 22 is less than the thickness of the hole 21, so that the top surface of the end plate 22 is lower than the top surface of the hole 21; a column 23 is vertically protruding upward on the top surface of each end plate 22, and the top surface of the column 23 is flush with the top surface of the hole 21.

[0023] The end plate 22 and the column 23 are stacked sequentially along the thickness direction of the hole 21, so that the top surface of the end plate 22 is formed as a first limiting step surface lower than the top surface of the hole 21, and the top surface of the column 23 is formed as a second limiting step surface flush with the top surface of the hole 21. The first limiting step surface and the second limiting step surface are staggered in the thickness direction, together forming the double-layer limiting structure.

[0024] The first limiting step surface is used to limit the position of the aluminum plate in the thickness direction, and the second limiting step surface is used to limit the position of the prepreg sheet in the thickness direction, so that the aluminum plate and the prepreg sheet are respectively limited to different thickness layers in the mold closing state, so as to achieve layered limiting and gapless bonding of the aluminum plate and the prepreg sheet in the thickness direction.

[0025] This double-layer limiting structure can simultaneously achieve precise "positioning" and "thickness determination" for two different materials: prepreg sheets and aluminum plates. Since the aluminum plate and prepreg sheets are precisely limited within the mold, the cured sample has neat edges and accurate dimensions, eliminating the need for any post-processing such as trimming or grinding. This allows for the efficient and reliable preparation of standardized test samples, avoiding micro-cracks, stress concentrations, or contamination that post-processing may cause to the bonding interface. It ensures that the subsequent roller peel test measures the material's true "intrinsic adhesion strength" rather than the "residual strength" after damage, thus removing obstacles in the sample preparation process.

[0026] The prepreg sheet has positioning holes that fit the column 23. The prepreg sheet is fitted onto the column 23 through the positioning holes in a snap-fit ​​manner, thereby achieving precise positioning of the prepreg sheet in the horizontal direction.

[0027] The aluminum plate is placed in the groove area between two opposing end plates 22. The inner sidewall of the end plate 22 forms a horizontal limit on the aluminum plate. The bottom surface of the aluminum plate is in contact with the top surface of the end plate 22 to achieve the positioning of the aluminum plate in the thickness direction.

[0028] The double-layer limiting structure simultaneously constrains the prepreg sheet and the aluminum plate in both the horizontal and thickness directions, ensuring that the sample obtained after molding and curing has neat edges and accurate dimensions, eliminating the need for trimming or grinding.

[0029] The height of the end plate 22 is equal to the thickness of the aluminum plate, and the height of the column 23 is equal to the thickness of the prepreg sheet. After the mold is closed, the distance between the inner surface of the upper mold plate 1 and the inner surface of the lower mold plate 3 is forcibly locked to the standard total thickness of the sum of the aluminum plate thickness and the prepreg sheet thickness.

[0030] The prepreg sheet is snapped directly onto the column 23 via its "positioning holes" for snap-on positioning; the aluminum plate is stably supported in the groove between the two end plates 22. The operator does not need to visually align or repeatedly adjust it; precise positioning can be achieved simply by placing it. This significantly reduces the difficulty of operation, avoids sample rejection due to human misalignment, and significantly improves sample preparation efficiency and yield.

[0031] The first and third layers are the upper and lower layers, respectively, forming a symmetrical structure, and are made of 304 stainless steel. The outer dimensions are 400*400*3mm. The second layer is the middle layer, which has a flat, hollowed-out design. It is made of 304 stainless steel, with an outer dimension of 400*400*4mm and an internal hollowed-out dimension of 360*60mm.

[0032] The height of the end plate 22 is equal to the height of the column 23, and the height of the column 23 is half the thickness of the hole 21, so that the column 23 and the end plate 22 are set through the hole 21.

[0033] The column 23 is used to fasten the prepreg sheet, and the area between the two opposing end plates 22 is used to accommodate the aluminum plate, with the bottom surface of the aluminum plate fitting against the top surface of the end plate 22.

[0034] After assembly, the lower surface of the prepreg sheet is attached to the top surface of the column 23, and the upper surface of the aluminum plate is attached to the inner surface of the upper template 1, so that the prepreg sheet and the aluminum plate are positioned without gaps in the thickness direction.

[0035] Epoxy resin-based prepregs flow under heat and pressure. If there are gaps between the prepreg sheet and the protrusions, the flowing resin may be squeezed into the gaps, resulting in a reduced resin content near the bonding interface, forming a resin-deficient zone, and significantly weakening the bond strength.

[0036] In this invention, the end plate 22 has a height of 2mm, precisely equal to the thickness of the aluminum plate, and the column 23 has a height of 2mm, precisely equal to the thickness of the prepreg sheet. After mold closing, the distance between the upper and lower surfaces inside the mold is forcibly locked to the standard total thickness of "aluminum plate + prepreg sheet". The gapless limiting ensures that the prepreg sheet is tightly supported by the column 23, and the resin can only overflow in a small amount in the horizontal direction. The resin at the interface is fully and uniformly retained, and the thickness of each sample is completely consistent. During the pressure curing process, all possible minor movements, thickness deviations, and resin loss that may affect the bonding quality are eliminated, thereby ensuring that the interface state of each sample is highly consistent, making the measured peel strength data true and repeatable.

[0037] The hot plate of the flat vulcanizing machine is usually 400×400mm, while the size of a single sample is 360mm×60mm. The middle template 2 has four holes 21 inside, which are arranged symmetrically.

[0038] The flat vulcanizing machine used in this invention is a flat vulcanizing machine purchased from China Machinery Precision Forming Industry Technology Research Institute (Anhui) Co., Ltd., specifically model QLLHY-50T.

[0039] The four holes 21 can simultaneously accommodate four sets of aluminum plates and prepreg sheets, allowing for the preparation of four roller-peeled samples in a single molding process. Compared to simple U-shaped molds or manual bonding that can only press one sample at a time, this method increases sample preparation efficiency by four times, accelerates the testing cycle, and facilitates rapid screening of aluminum plate surface treatment processes.

[0040] Meanwhile, the four holes 21 are located on the same intermediate template and undergo the exact same pressurization, heating, holding, and cooling processes. Therefore, the four samples produced within the same molding cycle exhibit highly consistent curing temperature history, pressure distribution, and resin flow behavior. This allows the four sets of data to be directly used to calculate the mean and standard deviation in subsequent roller peel tests, reducing process fluctuations caused by different batches and improving statistical reliability.

[0041] The surface of the intermediate template 2 is coated with polytetrafluoroethylene, which facilitates subsequent mold opening and template removal.

[0042] The upper template 1, lower template 3 and middle template 2 are all made of 304 stainless steel.

[0043] Both the upper template 1 and the lower template 3 have irregular protrusions 11 extending outwards on their edges. The irregular protrusions 11 are used to facilitate mold opening and sampling.

[0044] This mold frame serves as both a layup tooling and a mold shaping tooling. The design of the mold frame improves the efficiency of experimental sample production, speeds up the production cycle, and the fixed template effectively ensures the stability of the sample.

[0045] This mold adopts a three-layer structure of upper, middle and lower layers. The middle layer has a special structure that can serve as a shaping tool while ensuring the stability of the sample structure. It also has a built-in stepped structure and column, which effectively avoids the trouble of post-processing of the sample.

[0046] This invention significantly improves the adhesion between epoxy resin-based glass fiber composite materials and aluminum plates by applying a dual chemical coating and physical treatment to the surface of the aluminum plate.

[0047] like Figure 8 As shown, this application provides a method for testing the adhesion force between an aluminum plate and a composite material, comprising the following steps: S100. Provide an aluminum plate and a prepreg sheet, and cut and perforate the prepreg sheet to form positioning holes that can precisely fit with the subsequent mold. S200. The prepreg sheet is fastened onto the column of the mold through the positioning hole, and the aluminum plate is placed between the end plates of the mold. The double-layer limiting structure on the mold is used to simultaneously achieve precise positioning of the prepreg sheet and the aluminum plate and gapless limiting in the thickness direction. S300. The upper, middle and lower three-layer templates of the mold are combined to form a three-piece sandwich structure to forcibly lock the prepreg sheet. S400. The three-piece sandwich structure is placed in a molding equipment for molding, so that the prepreg sheet is cured and bonded to the aluminum plate to obtain a sample. The sample is taken out and clamped onto the corresponding matching fixture for a peel test.

[0048] In step S200, the lower surface of the prepreg sheet is attached to the top surface of the column, the bottom surface of the aluminum plate is attached to the top surface of the end plate, and the upper surface of the aluminum plate is attached to the inner surface of the upper template, so that the prepreg sheet and the aluminum plate are positioned without gaps in the thickness direction, and the total thickness of each sample is forcibly locked to a standard thickness value, ensuring that the thickness of multiple samples prepared in the same batch is consistent.

[0049] Consistent sample thickness, a smooth interface, and undamaged sample edges are prerequisites for obtaining stable and reliable data in roller peeling experiments. Manual bonding and layout can easily damage the sample if not handled carefully.

[0050] This invention involves cutting (determining the shape and size) and perforating a soft prepreg sheet to create positioning holes that allow for precise mating with subsequent molds. These positioning holes on the prepreg sheet are crucial for subsequent snap-fit ​​assembly. This eliminates the need for manual visual alignment during assembly, fundamentally reducing human error.

[0051] This invention achieves "snap-on" quick positioning through the cooperation of the column and the positioning hole, as well as the support of the aluminum plate by the end plate. The "snap-on" operation reduces the difficulty of sample preparation, can be completed quickly without skilled workers, and significantly improves the success rate of sample preparation.

[0052] Operators no longer need to visually align or repeatedly adjust; they simply attach the prepreg sheet to the column and then place the aluminum plate between the end plates. This significantly reduces operational difficulty and reliance on personnel skills, avoids sample scrapping due to human error, eliminates the need for "post-processing" of samples, removes secondary damage, and significantly improves sample preparation efficiency and yield.

[0053] Furthermore, the present invention uses positioning holes to "fasten" the prepreg sheet onto the column of the mold, while simultaneously placing the aluminum plate between the end plates of the mold. Utilizing the unique "double-layer limiting structure" of the forming mold, precise positioning and gapless limiting in the thickness direction of the two different materials (prepreg sheet and aluminum plate) are simultaneously achieved.

[0054] The gapless limiting mechanism forces the total thickness of each sample to be locked to the standard value, eliminating test errors caused by uneven thickness and ensuring the consistency of sample thickness. Furthermore, the prepreg sheet is tightly supported, preventing excessive resin loss or the formation of resin-deficient areas during the curing process, thus ensuring the integrity of the bonding interface.

[0055] The sample prepared by this method has neat edges and does not require subsequent cutting, thus avoiding microcracks or stress concentrations that may be caused to the bonding interface by secondary processing.

[0056] The mold can be designed with multiple holes (such as four), and multiple samples can be prepared at the same time in one molding, which improves efficiency several times. Moreover, the curing process of samples in the same batch is completely consistent, which increases the statistical reliability of the data.

[0057] A flat vulcanizing machine can be selected as the molding equipment, which serves to pressurize and heat the sample for preparation.

[0058] The prepreg sheet is an epoxy resin-based glass fiber prepreg sheet.

[0059] The peel test was a roller peel test, and the fixture was a roller peel test fixture. Since the preliminary sample preparation steps have minimized all possible sample preparation errors, the data fluctuations measured in this step mainly stem from the differences in the aluminum plate surface treatment process itself. Therefore, by comparing the peel strength measured under different processes, the optimal surface treatment process can be quickly and accurately determined, making the "sample preparation → testing and evaluation" cycle efficient and reliable, thereby accelerating the overall screening efficiency of the optimal aluminum plate surface treatment process.

[0060] The present invention uses a cleverly designed mold to transform the sample preparation process into a simple and reliable standardized operation, thereby transferring the variance of the test data from the sample preparation error to the material process itself. This improves the accuracy of the analysis of the experimental data and greatly enhances the efficiency of research and development and quality inspection.

[0061] Example 1:

[0062] 1. Selection of molding equipment (1) The molding equipment is called a flat vulcanizing machine, which consists of a motor, pressure gauge, hot plate and control panel. The parameters of the 25T 400×400×1 vulcanizing machine are shown in Table 1: Table 1

[0063] (2) The mold used is the molding mold disclosed in this invention; (3) A roller peeling test fixture was selected for the peeling test; (4) The prepreg is bisphenol A type epoxy resin with a resin content of 45%; (5) The fabric type of the glass fiber reinforced material is twill fabric with a basis weight of 450 g / m. 2 .

[0064] 2. Sample making (1) Cut the prepreg according to the design size to ensure that the shape and size of each layer are accurate and meet the requirements of the template for the roller peeling mold. For the components with holes at both ends, cut the blanks into specific shapes to facilitate the fit of the mold outline during laying and ensure molding efficiency. The sample size is 360mm*60mm*2mm and the diameter of the opening at both ends is M5. (2) Lay-up steps: Place the 360*60*2mm prepreg sheet into the mold frame, and after positioning, place the 300*60*2mm aluminum plate on the back of the prepreg. Four templates can be placed on one middle mold frame. (3) Install the upper and lower pressure plates on the mold frame to form a three-piece sandwich structure, and place this structure in the molding equipment for molding and curing; The molding parameters are as follows: temperature: 148~152℃; molding pressure: 0.5MPa~1.5MPa; holding time: 8min; heating rate: constant temperature; finally, the mold is opened and samples are taken directly in the hot mold state.

[0065] The curing parameters are: temperature: 138℃~145℃; pressure: approximately 0.5MPa~1.5MPa; time: 8min.

[0066] 3. Peeling test After the roller passes through the molded layer and is molded, the roller peeling sample is removed and clamped onto the corresponding matching fixture for peeling test.

[0067] Roller specifications: Diameter: 100mm ± 0.10mm; Roller material: Aluminum alloy; Clamp weight: 1.5kg; Loading method: Tension; The roller running speed range is 5 mm / min, the roller peeling angle is determined by 90° peeling, and the peeling force is sampled continuously.

[0068] For details, please refer to GB / T 1457-2022 "Test Method for Peel Strength of Sandwich Structures".

[0069] 4. Experimental results of aluminum plate composite material products (1) The results of the composite roller peeling test of 2mm thick aluminum plate + 450g prepreg from Lily Aerospace at 150℃ are shown in Table 2: Table 2

[0070] (2) The results of third-party tests on epoxy resin-based glass fiber composite materials and electrophoretic steel plates are shown in Table 3:

[0071] 5. Conclusion Analysis The success rate of sample making using the mold in this case is 100%, while the existing method is only 50-70%, which greatly improves the success rate of sample making.

[0072] After undergoing original color oxidation and wire drawing, aluminum plates exhibit the best bonding ability with epoxy resin-based glass fiber composite materials, surpassing anodized aluminum and mainstream electrophoretic steel plates.

[0073] This testing method enhances the interlayer adhesion between the aluminum plate and the epoxy resin-based glass fiber composite material, avoiding the risk of misalignment and detachment of the automotive undercarriage pallet, and providing more options for the future manufacture of automotive undercarriage pallet products.

[0074] In summary, this invention eliminates the interference of variables in the sample preparation process, so that the fluctuations in the measured data (such as the multiple tests of the same sample in Table 2 of the examples) mainly come from the differences in the surface treatment process of the aluminum plate itself, rather than the sample preparation error. This improves the efficiency of screening the best aluminum plate surface treatment process, as verified by the successful screening of "original color anodized wire drawing" in the examples, which is superior to other processes.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. All such modifications or substitutions should be covered within the protection scope of this application, and should not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application. Therefore, the protection scope of this application should be determined by the protection scope of the claims.

Claims

1. A mold for testing the adhesion force between aluminum plates and composite materials, characterized in that, Including the upper template (1), the lower template (3), and the middle template (2); The upper template (1) and the lower template (3) are surface-symmetrical structures; The intermediate template (2) is a flat plate with a hole design, and has at least one hole (21) inside for accommodating the prepreg sheet and aluminum plate. The end plate (22) protrudes from the bottom surface of the hole (21), and the height of the end plate (22) is less than the thickness of the hole (21), so that the top surface of the end plate (22) is lower than the top surface of the hole (21); a column (23) is vertically protruding upward on the top surface of each end plate (22), and the top surface of the column (23) is flush with the top surface of the hole (21); The end plate (22) and the column (23) are stacked sequentially along the thickness direction of the hole (21), such that the top surface of the end plate (22) is formed as a first limiting step surface lower than the top surface of the hole (21), and the top surface of the column (23) is formed as a second limiting step surface flush with the top surface of the hole (21). The first limiting step surface and the second limiting step surface are staggered in the thickness direction, together forming the double-layer limiting structure. The first limiting step surface is used to limit the position of the aluminum plate in the thickness direction, and the second limiting step surface is used to limit the position of the prepreg sheet in the thickness direction, so that the aluminum plate and the prepreg sheet are respectively limited to different thickness layers in the mold closing state, so as to achieve layered limiting and gapless bonding of the aluminum plate and the prepreg sheet in the thickness direction.

2. The mold according to claim 1, characterized in that, The prepreg sheet has a positioning hole that matches the column (23). The prepreg sheet is fitted onto the column (23) through the positioning hole in a snap-fit ​​manner, thereby achieving precise positioning of the prepreg sheet in the horizontal direction. The aluminum plate is placed in the groove area between two opposing end plates (22), the inner sidewall of the end plate (22) forms a horizontal limit on the aluminum plate, and the bottom surface of the aluminum plate is in contact with the top surface of the end plate (22) to achieve the positioning of the aluminum plate in the thickness direction. The double-layer limiting structure simultaneously constrains the prepreg sheet and the aluminum plate in both the horizontal and thickness directions, ensuring that the sample obtained after molding and curing has neat edges and accurate dimensions, eliminating the need for trimming or grinding.

3. The mold according to claim 2, characterized in that, The height of the end plate (22) is equal to the thickness of the aluminum plate, and the height of the column (23) is equal to the thickness of the prepreg sheet. After the mold is closed, the distance between the inner surface of the upper mold plate (1) and the inner surface of the lower mold plate (3) is forcibly locked to the standard total thickness of the sum of the aluminum plate thickness and the prepreg sheet thickness.

4. The mold according to claim 2, characterized in that, The intermediate template (2) has a number of holes (21) inside. The holes (21) are evenly spaced along the length of the intermediate template (2). Each hole (21) is provided with an end plate (22) and a column (23), so that several samples can be prepared simultaneously in one molding cycle, and the curing temperature history, pressure distribution and resin flow behavior of several samples are consistent in the same molding cycle.

5. The mold according to claim 1, characterized in that, The intermediate template (2) is coated with polytetrafluoroethylene.

6. The mold according to claim 1, characterized in that, The inner surfaces of the upper template (1) and the lower template (3) are both mirror polished.

7. The mold according to claim 1, characterized in that, The edges of the upper template (1) and the lower template (3) are provided with irregular protrusions (11) extending outwards. The irregular protrusions (11) are used to facilitate mold opening and sampling.

8. A method for testing the adhesion force between an aluminum plate and a composite material, characterized in that, The testing method is based on a test sample prepared using the mold described in any one of claims 1-7, and includes the following steps: S100. Provide an aluminum plate and a prepreg sheet, and cut and perforate the prepreg sheet to form positioning holes that can precisely fit with the subsequent mold. S200. The prepreg sheet is fastened onto the column of the mold through the positioning hole, and the aluminum plate is placed between the end plates of the mold. The double-layer limiting structure on the mold is used to simultaneously achieve precise positioning of the prepreg sheet and the aluminum plate and gapless limiting in the thickness direction. S300. The upper, middle and lower three-layer templates of the mold are combined to form a three-piece sandwich structure to forcibly lock the prepreg sheet. S400. The three-piece sandwich structure is placed in a molding equipment for molding, so that the prepreg sheet is cured and bonded to the aluminum plate to obtain a sample. The sample is taken out and clamped onto the corresponding matching fixture for a peel test.

9. The test method according to claim 8, characterized in that, In step S200, the lower surface of the prepreg sheet is attached to the top surface of the column, the bottom surface of the aluminum plate is attached to the top surface of the end plate, and the upper surface of the aluminum plate is attached to the inner surface of the upper template, so that the prepreg sheet and the aluminum plate are positioned without gaps in the thickness direction, and the total thickness of each sample is forcibly locked to a standard thickness value, ensuring that the thickness of multiple samples prepared in the same batch is consistent.

10. The test method according to claim 8, characterized in that, The prepreg sheet is an epoxy resin-based glass fiber prepreg sheet; The peeling experiment is a roller peeling experiment, and the fixture is a roller peeling experiment fixture.